A Brief History of Bioinformatics Told by Data Visualization - Mariano, Diego; Ferreira, Mívian; Sousa, Bruno L.; Santos, Lucianna H.; de Melo-Minardi, Raquel C. (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2020: Anais do XIII Simpósio Brasileiro de Bioinformática, 2020)
Bioinformatics is an interdisciplinary research field that aims to analyze biological data through computational approaches. In the last years, the evolution of technological resources has provided a tidal wave of biological data. Consequently, an unprecedented amount of studies using bioinformatics approaches have been released, increasing peer-reviewed published papers. Here, we tell a brief history of bioinformatics based on literature data analysis and visualization. We collected abstracts and other metadata from papers published from 1998 to 2019 in four leading bioinformatics journals: (i) Oxford Bioinformatics; (ii) BMC Bioinformatics; (iii) Briefings in Bioinformatics; and (iv) PLoS Computational Biology. Our results show an increase in publication number and international collaborations. We also observed an increase in publications by Chinese authors. Latin America continues to have a low percentage of global scientific bioinformatics production. However, Brazil excels in this region, being responsible for almost half of Latin America papers published. Our results also point out the recent trend of using Python as the programming language for bioinformatics applications, followed by Perl, Java, and R. We hope these data visualizations can provide insights to understand the recent changes and evolution in the bioinformatics field. The developed interactive visualizations are available at http://bioinfo.dcc.ufmg.br/history/.